2010
DOI: 10.1145/1644001.1644009
|View full text |Cite
|
Sign up to set email alerts
|

Optimizations for quadrature representations of finite element tensors through automated code generation

Abstract: We examine aspects of the computation of finite element matrices and vectors which are made possible by automated code generation. Given a variational form in a syntax which resembles standard mathematical notation, the low-level computer code for building finite element tensors, typically matrices, vectors and scalars, can be generated automatically via a form compiler. In particular, the generation of code for computing finite element matrices using a quadrature approach is addressed. For quadrature represen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 15 publications
0
86
0
Order By: Relevance
“…It includes several components such as DOLFIN (Logg and Wells, 2010;Logg et al, 2012c), FFC (Kirby and Logg, 2006;Logg et al, 2012b;Ølgaard and Wells, 2010) and FIAT (Kirby, 2004(Kirby, , 2012, which enable automatic solution of linear and non-linear problems once the variational forms of the PDEs are expressed in the Unified Form Language (UFL; Alnaes et al, 2014;Alnaes, 2012).…”
Section: Fenics Softwarementioning
confidence: 99%
“…It includes several components such as DOLFIN (Logg and Wells, 2010;Logg et al, 2012c), FFC (Kirby and Logg, 2006;Logg et al, 2012b;Ølgaard and Wells, 2010) and FIAT (Kirby, 2004(Kirby, , 2012, which enable automatic solution of linear and non-linear problems once the variational forms of the PDEs are expressed in the Unified Form Language (UFL; Alnaes et al, 2014;Alnaes, 2012).…”
Section: Fenics Softwarementioning
confidence: 99%
“…As the mathematical structure of the PDE is available for analysis, important equation-specific optimisations may be performed that low level compilers cannot automate, or that would be too laborious to implement by hand [7,8]. UFL is remarkably compact: a finite element discretisation that might take thousands or tens of thousands of lines of FORTRAN or C++ code to implement can be cleanly expressed in just a handful of lines of UFL.…”
Section: Automated Code Generation In Computational Sciencementioning
confidence: 99%
“…The FEniCS form compiler also performs other optimizations for for quadrature based code generation [Ølgaard and Wells 2010]. Firstly, if a basis function or its derivatives evaluate to zero at all quadrature points, operations on those values can be eliminated.…”
Section: Quadraturementioning
confidence: 99%
“…Work by Ølgaard and Wells [Ølgaard and Wells 2010] has shown that for some variational forms, the tensor contraction representation of assembly outperforms quadrature by a factor of 300 in terms of operation count. However, for other forms, quadrature representation can outperform tensor contraction by a factor of 100.…”
Section: Introductionmentioning
confidence: 99%